A review on competitive pricing in supply chain management problems: models, classification, and applications. (26th November 2021) - Ziari, Matineh; Ghomi‐Avili, Morteza; Pishvaee, Mir Saman; Jahani, Hamed
Abstract: Supply chain management (SCM) deals with various strategic, tactical, and operational level decisions in which pricing is of utmost importance to decision makers. Most of the real‐life supply chain pricing problems consider competition as a crucial factor in order to expand the market share and tackle emerging competitors. Accordingly, competitive pricing in SCM has attracted great attention by practitioners and academicians in the last four decades. Now after 40 years, it seems necessary to systematically review and classify the previous studies and present the most appealing future research directions. This paper provides a comprehensive review of the state‐of‐the‐art published papers in scientific journals. Here, 166 papers published from 1983 to 2021 are reviewed and classified to introduce the major models and specific considerations in this field. After reviewing the selected competitive pricing models, some research insights and potential subjects for extending the literature are presented to illustrate the most appropriate and challenging future research directions.